Obstructive Meckel’s diverticulum in a renal transplant recipient: a case report and intraoperative enteroscopy findings - Lopez, Salvador Zadur Kaloyan; Verdugo Salazar, Carlos Israel; Coutiño, Luis Fernando Gálvez; Bezies, Yamir Ahmed Nacud; Rios, Casandra Rosas (International Surgery Journal, 2025)
Meckel’s diverticulum, the most common congenital anomaly of the gastrointestinal tract, is often asymptomatic but may lead to bleeding, obstruction, or inflammation. In renal transplant recipients, immunosuppression and overlapping symptoms can obscure diagnosis. We present a 37-year-old male renal transplant recipient with chronic obscure gastrointestinal bleeding, anemia, and diarrhea. His complex medical history included end-stage renal disease due to vesicoureteral reflux, multiple immunosuppressive therapies, and prior transplant rejection episodes. Initial endoscopic studies revealed nonspecific findings. Capsule endoscopy identified a submucosal lesion suggestive of Meckel’s diverticulum, and imaging showed mural thickening and graft atrophy. Surgical exploration with intraoperative enteroscopy confirmed a 2.5 cm Meckel’s diverticulum 50 cm from the ileocecal valve, alongside lymphangiectasias and arteriovenous malformations. Segmental small bowel resection with side-to-side enteroenteric anastomosis was performed. The patient recovered uneventfully. Histopathology demonstrated chronic inflammation and recent hemorrhage, with no evidence of malignancy. Meckel’s diverticulum, though rare in adults, should be considered in transplant recipients presenting with obscure gastrointestinal bleeding. Capsule endoscopy and intraoperative enteroscopy proved invaluable for diagnosis. Surgical resection remains the treatment of choice in symptomatic cases. Multidisciplinary management is essential in immunosuppressed patients with complex gastrointestinal symptoms.